2011
DOI: 10.1096/fj.11-193193
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during pregnancy mitigates Alzheimer‐like pathology in mouse offspring

Abstract: Physical activity protects brain function in healthy individuals and those with Alzheimer's disease (AD). Evidence for beneficial effects of parental exercise on the health status of their progeny is sparse and limited to nondiseased individuals. Here, we questioned whether maternal running interferes with offspring's AD-like pathology and sought to decipher the underlying mechanisms in TgCRND8 mice. Maternal stimulation was provided by voluntary wheel running vs. standard housing during pregnancy. Following 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 53 publications
3
48
1
Order By: Relevance
“…magnification, numerical aperture 1.4) (all objectives from NIKON), a color digital camera (3/4 00 chip, 36-bit color, DV-20, MicroBrightField), and MicroBrightField software were used. Ab plaques (1:100, 6F/3D, DAKO), microglia (AIF1, 1:100, APO8912PU-N, Acris), and cerebral vessels (laminin, 1:300, L9393, Sigma-Aldrich) were visualized and stereologically quantified in 10 sections (with 100 mm interspace between sections) per staining and animal as previously described [28] with minor modifications. Briefly, Ab plaque load was quantified at 200!…”
Section: In Vivo Approachmentioning
confidence: 99%
“…magnification, numerical aperture 1.4) (all objectives from NIKON), a color digital camera (3/4 00 chip, 36-bit color, DV-20, MicroBrightField), and MicroBrightField software were used. Ab plaques (1:100, 6F/3D, DAKO), microglia (AIF1, 1:100, APO8912PU-N, Acris), and cerebral vessels (laminin, 1:300, L9393, Sigma-Aldrich) were visualized and stereologically quantified in 10 sections (with 100 mm interspace between sections) per staining and animal as previously described [28] with minor modifications. Briefly, Ab plaque load was quantified at 200!…”
Section: In Vivo Approachmentioning
confidence: 99%
“…A similar study found that, in mice, maternal running during pregnancy and nursing resulted in a 40% increase in total granule cells in the offspring hippocampus (2). Recently, Herring et al (19) showed that short-term exercise during pregnancy was able to reduce Alzheimer pathology in offspring in a transgenic mouse model that is predisposed to the disease. Exercise during pregnancy can clearly affect many maternal and offspring outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…Maternal swimming activity resulted in increased reactive oxygen species in the cerebellum, parietal cortex and hippocampus in postnatal day 7 offspring This group also had reduced mitochondrial superoxide in the cerebellum and parietal cortex but increased nitrate levels in the cerebellum, parietal cortex, hippocampus, and striatum Antioxidant activity, catalase, and glutathione-peroxidase was increased in the cerebellum, parietal cortex and hippocampus for the maternal exercise offspring Superoxide dismutase was increased only in the parietal cortex of this offspring group Mitochondrial mass and membrane potential were increased in the cerebellum and parietal cortex of pups from exercised dams 55 Female transgenic (TG) CRND8 mice, who hemizygously carry the human APP 695 transgene on a hybrid C57Bl/6-C3H/HeJ background and are considered a good mouse model for Alzheimer's disease…”
Section: Maternal Exercise and Offspring Behavioral And Reproductive mentioning
confidence: 84%